Answer:
Yes
![y=e^(-11x)=(1)/(e^(11x))=(1)/(e^(11)) (1)/(e^x)=(1)/(e^(11)) e^(-x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/43njesy8ib7hmzk5k88101zu82sac76le5.png)
So then we see that the base on this case is:
, so then our function can be considered as an exponential function.
Explanation:
First we need to define an exponential function.
The exponential function with a base c is givn by the following expression:
, and
and x can be any real number.
The exponential function have always a base and a variable. The value c it's called the base and x the variable.
The exponential function is defined as:
![y=e^x](https://img.qammunity.org/2020/formulas/mathematics/high-school/3ea6q077oj4yctdar41dxuhse4q25gd61e.png)
And the function given by:
is called the natural exponential function.
For our special case our function is given by:
![y=e^(-11x)=(1)/(e^(11x))=(1)/(e^(11)) (1)/(e^x)=(1)/(e^(11)) e^(-x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/43njesy8ib7hmzk5k88101zu82sac76le5.png)
So then we see that the base on this case is:
, so then our function can be considered as an exponential function.